2016
DOI: 10.1038/npp.2016.35
|View full text |Cite
|
Sign up to set email alerts
|

SSRI Augmentation by 5-Hydroxytryptophan Slow Release: Mouse Pharmacodynamic Proof of Concept

Abstract: Drugs, notably SSRIs, that elevate brain extracellular 5-HT (5-HT Ext ) are antidepressants. Unfortunately, most patients fail to remit. Multipronged clinical evidence suggests that elevating 5-HT Ext beyond the SSRI effect enhances antidepressant efficacy, but previous such drug strategies had prohibitive limitations. In humans, adjunct treatment with the 5-HT precursor 5-hydroxytryptophan (5-HTP) elevates 5-HT Ext beyond the SSRI effect. Small pilot trials suggest that adjunct 5-HTP can confer antidepressant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 53 publications
3
26
0
Order By: Relevance
“…In contrast, 5-HTP readily crosses the BBB and can be converted into 5-HT. Therapeutic 5-HTP has also been shown to treat clinical depression with a potency equivalent to or better than SSRIs (Birdsall, 1998;Jangid et al, 2013;Jacobsen et al, 2016). Furthermore, B. infantis intake increased plasma TRP levels in healthy rats (Desbonnet et al, 2008), but another study with chronic-stressed rats reported otherwise (Desbonnet et al, 2010).…”
Section: Butyrate Trp and Central 5-ht-bdnf Systemmentioning
confidence: 99%
“…In contrast, 5-HTP readily crosses the BBB and can be converted into 5-HT. Therapeutic 5-HTP has also been shown to treat clinical depression with a potency equivalent to or better than SSRIs (Birdsall, 1998;Jangid et al, 2013;Jacobsen et al, 2016). Furthermore, B. infantis intake increased plasma TRP levels in healthy rats (Desbonnet et al, 2008), but another study with chronic-stressed rats reported otherwise (Desbonnet et al, 2010).…”
Section: Butyrate Trp and Central 5-ht-bdnf Systemmentioning
confidence: 99%
“…The dose of 5-HTP (5 mg/kg) in the present study was comparable with the clinical dose range of 200 to 300 mg/day, typically administered per os or intravenous 24 . Furthermore, a slow-release (SR) formulation of 5-HTP has been shown to provide more stable increases in 5-HT concentration, with less adverse effects, than the immediate-release form in rodent studies 58 . Therefore, PET measurement with [ 11 C]AZ10419369 and pretreatment with oral administration of 5-HTP SR is a promising paradigm to investigate 5-HT release in the human brain.…”
Section: Discussionmentioning
confidence: 99%
“…Directed by the clinical data reviewed above we carried out an adjunctive 5-HTP SR proof-of-concept study in mice [83]. We modeled 5-HTP SR using subcutaneous minipumps, which produces constant (zero-order) SR delivery.…”
Section: In Mouse Models 5-htp Sr Transforms the Therapeutic Potentimentioning
confidence: 99%
“…Such slower metabolism could account for the observed longer human T 1/2 of 5-HTP (2h) vs. L-DOPA (1h) [94]. In mice, in a study discussed in the main text, we determined the T 1/2 to be about 12 min [83], 10 times faster than in humans, in accordance with the typical mouse:human metabolism and dose-extrapolation scaling factor of about 10 [95]. …”
Section: Figurementioning
confidence: 99%